Quantitative T2 MRI for bone marrow iron overload: normal reference values and assessment in thalassemia major patients - Meloni, Antonella; Pistoia, Laura; Restaino, Gennaro; Missere, Massimiliano; Positano, Vincenzo; Spasiano, Anna; Casini, Tommaso; Cossu, Antonella; Cuccia, Liana; Massa, Antonella; Massei, Francesco; Cademartiri, Filippo (Radiologia medica, 2022)
Purpose We evaluated the feasibility and reproducibility of bone marrow T2* values and established the lower limit of normal in a cohort of healthy subjects. We investigated the clinical correlates of bone marrow T2* values in patients with thalassemia major (TM). Material and Methods Thirty healthy subjects and 274 consecutive TM patients (38.96 ± 8.49 years, 151 females) underwent MRI at 1.5T. An axial slice in the upper abdomen was acquired by a T2* gradient-echo multiecho sequence and the T2* value was calculated in a circular region of interest defined in the visible body of the first or second lumbar vertebra. In patients, also liver and heart T2* values were assessed. Results In healthy subjects bone marrow T2* values were independent of age and gender. The lower limit of normal for bone marrow T2* was 13 ms. In both healthy subjects and 30 randomly selected patients, the coefficient of variation for inter-operator-reproducibility was < 10%. TM patients exhibited significantly lower bone marrow T2* values than healthy subjects (7.47 ± 5.18 ms vs. 17.08 ± 1.89 ms; p < 0.0001). A pathological bone marrow T2* was detected in 82.8% of TM patients. In TM, the female sex was associated with reduced bone marrow T2* values. Bone marrow T2* values were inversely correlated with mean serum ferritin levels (R = -0.431; P < 0.0001) and hepatic iron load ( R = − 0.215; P < 0.0001). A serum ferritin level > 536 ng/ml predicted the presence of a pathological bone marrow T2*. A positive correlation was found between bone marrow and heart T2* values ( R = 0.143; P = 0.018). A normal bone marrow T2* showed a negative predictive value of 100% for cardiac iron. Conclusion Bone marrow T2* measurements can be easily obtained using the same sequences acquired for liver iron quantification and may bring new insights into the pathophysiology of iron deposition; hence, they should be incorporated into clinical practice.